CAB abstracts on CD-ROM - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
CAB International has publish ed its database from 1984 on CD-ROM. This is in response to considerable demand from customers wanting easy access to the full bibliographic details and informative abstracts for which CABI is recognized through the...